2020
DOI: 10.3390/ijms21228530
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Counteracts Vascular Calcification In Vitro Through an Early Up-Regulation of SOD2 Based on a Transcriptomic Approach

Abstract: Vascular calcification (VC) is a critical contributor to the rising cardiovascular risk among at-risk populations such as those with diabetes or renal failure. The pathogenesis of VC involves an uprising of oxidative stress, for which antioxidants can be theoretically effective. However, astaxanthin, a potent antioxidant, has not been tested before for the purpose of managing VC. To answer this question, we tested the efficacy of astaxanthin against VC using the high phosphate (HP)-induced vascular smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Astaxanthin, is a carotenoid derivative found in the red pigments of crustacean shells and salmons with known potent antioxidative effect. High phosphate concentration treated VSMCs showed reduced pro-calcifying properties when exposed to astaxanthin [ 199 ]. Mitoquinone (a mitochondria-targeting antioxidant formed by covalently binding ubiquinone or coenzyme Q) attenuated VC by suppressing oxidative stress and apoptosis of VSMCs through the Keap1/Nrf2 pathway [ 200 ].…”
Section: Possible Therapeutic Strategiesmentioning
confidence: 99%
“…Astaxanthin, is a carotenoid derivative found in the red pigments of crustacean shells and salmons with known potent antioxidative effect. High phosphate concentration treated VSMCs showed reduced pro-calcifying properties when exposed to astaxanthin [ 199 ]. Mitoquinone (a mitochondria-targeting antioxidant formed by covalently binding ubiquinone or coenzyme Q) attenuated VC by suppressing oxidative stress and apoptosis of VSMCs through the Keap1/Nrf2 pathway [ 200 ].…”
Section: Possible Therapeutic Strategiesmentioning
confidence: 99%
“…We harnessed an experimental model of VC established previously [ 10 , 11 , 15 ] for testing identified compounds. Briefly, a VSMC cell line, A7r5, between 3 and 6 passages was obtained from American Type Culture Collection, plated onto 24- and 6-well plates, and cultured with Dulbecco's modified Eagle's medium (DMEM) supplemented with fetal bovine serum (FBS), streptomycin/penicillin in 5% ambient CO 2 under 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Druggable targets inherent to the pathogenic landscape of VC can also be discovered through similar strategies. Using a transcriptomic approach followed by experimental validation, we previously showed that astaxanthin might beneficially influence VC severity through its action toward superoxide dismutase 2 (SOD2) [ 15 ]. Machine learning, a new strategy and expanding research discipline that trains computers to learn from massive data, emerges as a promising tool to help mine patterns or linkages [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium has also been shown to ameliorate oxidative stress and decrease vascular calcification severity through its effect on multiple pathways, including SM22 regulation [ 68 ]. Finally, using an in vitro model of VSMC calcification in combination with transcriptomic profiling, our research group recently discovered that astaxanthin, a carotenoid derivative with strong antioxidative property, exhibited a prominent anticalcific effect through specifically targeting SOD2 during treatment of calcified VSMCs [ 69 ]. Indeed, there are a handful of natural products or extracts exhibiting in vitro or in vivo effects of augmenting Sod2 expression and activities [ 70 , 71 ], and testing these SOD2-targeted candidates in VSMCs regarding their anticalcific potential may be a fruitful approach for identifying new pharmaceuticals for treating vascular calcification.…”
Section: Sod2-targeted Strategies In Vascular Calcification Managementioning
confidence: 99%